Perspectives, Practices And Understanding Of Yoga In Modern Era (Journal of Namibian Studies : History Politics Culture, 2023)
The purpose of the study was to find out the changing perspectives-practices-understanding of Yoga in the modern era. Yoga has become popular and commercialized so authentic practices of yoga become very much modified. Many yoga teachers have a wrong understanding about the concept of Yoga. The purpose of the study, 20 yoga studios of Pune city were randomly selected for observation. Their style of teaching Yoga and methods of classes. After observing 20 yoga studios, it was observed that the many Yoga studios teach modification in Yoga classes. Traditional way of practicing yoga for example – Raja Yoga/Patanjal Yoga, Karma Yoga, Hatha Yoga, Jnyana Yoga, Nath Yoga, Bhakti Yoga, Mantra Yoga, Laya Yoga etc. and modern way of practicing Yoga - Hot yoga, Power yoga, Beer yoga, Wine yoga etc. so the real purpose of yoga is not fulfilled here by them. There is a need to increase more awareness about traditional yoga. The experimental results show that the modern methods are correctable by giving them the right material of yoga and to make people Yoga as a lifestyle.